Modulation of Keap1/Nrf2/ARE Signaling Pathway by Curcuma- and Garlic-Derived Hybrids - Serafini, Melania Maria; Catanzaro, Michele; Fagiani, Francesca; Simoni, Elena; Caporaso, Roberta; Dacrema, Marco; Romanoni, Irene; Govoni, Stefano; Racchi, Marco; Daglia, Maria; Rosini, Michela; Lanni, Cristina (Frontiers in Pharmacology, 2020)
Nrf2 is a basic leucine zipper transcription factor that binds to the promoter region of the antioxidant response element (ARE), inducing the coordinated up-regulation of antioxidant and detoxification genes. We recently synthesized a set of new molecules by combining the functional moieties of curcumin and diallyl sulfide, both known to induce the expression of antioxidant phase II enzymes by activating Nrf2 pathway. The aim of the study is to investigate the ability of such compounds to activate Keap1/Nrf2/ARE cytoprotective pathway, in comparison with two reference Nrf2-activators: curcumin and dimethyl fumarate, a drug approved for the treatment of relapsing-remitting multiple sclerosis. Furthermore, since Nrf2 pathway is known to be regulated also by epigenetic modifications, including key modifications in microRNA (miRNA) expression, the effects of the hybrids on the expression levels of selected miRNAs, associated with Nrf2 signaling pathway (miR-125b-5p and miR-196a-5p), have also been investigated. The results show that compounds exert antioxidant effect by activating Nrf2 signaling pathway and inducing the ARE-regulated expression of its downstream target genes, such as HO-1 and NQO1, with two hybrids to a higher extent than curcumin. In addition, some molecules induce changes in the expression levels of miR-125b-5p, even if to a lesser extent than curcumin. However, no changes have been observed in the expression levels of mRNA coding for glutathione synthetase, suggesting that the modulation of this mRNA is not strictly under the control of miR-125b-5p, which could be influenced by other miRNAs.